The causes of Caribbean and African diasporic movements in Lakshmi Persaud’s Sastra and Caryl Phillips’s the Nature of Blood - Mohammed Wagaa, Intisar; Mani, Manimangai; Talif, Rosli; Bahar, Ida Baizura (Center for Resource, Research and Publication Services, 2019)
This study approaches Lakshmi Persaud’s Sastra(1993) and Caryl Phillips’s The Nature of Blood(1997) form apostcolonial perspective. Therefore, the research will apply Homi Bhabha’s concept of displacement to examine the reasons of forced movement in the selected works which has been rarely applied. It will also apply the concept of synergy to explore the synergetic identity in these novels. The concept of synergy is hardly applied to analyze the changing identity depicted in the selected works. The synergetic identity will be argued as the preceding identity change that paves the way for the characters’ hybrid identity. In this sense, the synergetic identity will be limited to the analysis of the characters’initial influence by the host land’s culture and traditions. Robert Young’s concept of synergy will be applied to reveal the host land’s basic influence upon the displaced people’s identity. Then, they gradually amalgamate with the host land’speople. By time, the displaced people’s identity becomes hybrid; i.e., consisting of two discrepant culture, the homeland’s culture and the host land’s culture. Additionally, utilizing the concept of hybridity is scarcely used to analyze the novels’embodiment of colonial synergy and displacement. Consequently, my research will argue that both Persaud and Phillip in directly critique the oppressed and displaced people in order to elevate their socio-cultural status in the world. Thus,the function of synergy will be the interpretation of hybridity caused by colonial displacement. In this regard, Persaud and Phillips provide a comprehensive depiction of the African and Caribbean forced diasporic displacement through the portrayal of the characters’ immigration; which is the main cause of their synergetic hybridity formed in the demarcation of the host land. Thus, the study unravels the synergetic hybrid identity, as conceived by Persaud and Phillips, to exalt the position of the displaced African and Indo-Caribbean people.